Die koninkryk van God as sistematies-teologiese kategorie in die werk van J.A. Heyns - Marais, Sarel J. L. (Verbum et ecclesia, 2011)
The kingdom of God as a systematic-theological category in the work of J.A. Heyns Heyns was probably the most noteworthy Afrikaans speaking theologian of the 20th century, considering the quantity of Afrikaans theological publications from his pen. It is a well known fact that he used the kingdom of God as a systematic-theological category that flows like a perennial river of opportunity through all of his writings. It created an opportunity to be consistent in both his systematic theology and in his ethics, show clearly how man and God can be coworkers in a dialogical relationship and to integrate philosophy with theology. Unfortunately, there was sometimes flooding, because he filled the kingdom of God with philosophical concepts and viewed it as an ontological cosmic-universal entity. His philosophical background also occasionally led to inadequate speculations in his theology and inadmissibly he didn’t always use the Bible appropriately, although his doctrine of Scripture and hermeneutics were satisfactory. Lastly, his philosophical modus operandi helped him to differentiate between important theological concepts, which have problem solving abilities.